FIRST LANGUAGE ACQUISITION FOR CHILDREN AGED 3-4 YEARS IN SEBERANG ULU 1 KERTAPATI PALEMBANG - Maida, Maida; Wahidy, Achmad; Effendi, Darwin (Universitas PGRI Palembang, 2023)
This study aims to describe the acquisition of first language in children aged 3-4 years at Seberang Ulu 1 Kertapati Palembang with a total of 4 children who have different ages in the phonology and morphology study level. The research method used is descriptive qualitative method. Data collection techniques used in this study were observation techniques, recording techniques, listening techniques, interview techniques and note taking techniques. The data analysis technique used is descriptive analysis technique. Therefore, the difficulty that often arises in analyzing novels is having to read Keywords : First language acquisition, phonology, morphology, Palembang, and language acquisition studies